Economics with a phylogenetic signature - Kurt Dopfer (Max Planck Institute of Economics, 2013)
Ever since Darwin biologists have emphasised the commonalities between non-human and human species, while anthropologists have stressed the big difference between them. This paper not only endorses commonalities between species but takes them as a means to give extant phylogenetic differences a clear profile. It introduces the notion of universal culture, applicable to all phylogenies of culture-making species. Culture is defined as a system of socially generated and transmitted rules that allow their carrier cultural operations, economic operations taking centre stage in the study. Based on explorative induction - employing macaques washing sweet potatoes and 60,000-year-old ornamented ostrich eggs as exemplars - commonalities and differences between the cultures of non-human and human primates are highlighted. The hypothesis is advanced that non-human primates are capable of endosomatic culture, meaning that the origination of their culture is conditional upon a sensory nexus between the rule maker and the external referent; for instance, a tool rule is originated by inferring a tool function from the shape of a pre-existing stone. In contrast, humans can evolve exosomatic culture, as they possess the unique ability of imagination, which enables them to originate rules independent of any sensory nexus. Genetically equipped with the ability to use abstract language, humans can transmit rules both horizontally and vertically, not just as object-dependent templates but also as symbols. The possession of shared imagination is seen as representing the major proximate cause of the evolution of human culture, facilitating its distinctive economic operations.
Keywords: 330